Nitrogen potassium fertilization and soil-moisture effects on growth and development of drip-irrigated sugarcane - Ingram, K.T.; Hilton, H.W. (Wiley, 1986)
Because of the lack of N‐K balance in previous experiments and because of the relatively new development of drip irrigation, field research was conducted to determine the effects of N‐K fertilization and soil moisture on the growth and development of drip‐irrigated sugarcane (Saccharum spp. hybrids). Two levels of N‐K fertilization, 575‐551 and 225‐217 kg ha−1, were applied in factorial combination with three soil moisture regimes: (i) maintaining soil moisture tension between 10 and 20 kPa through frequent irrigation (designated 10‐20); (ii) maintaining soil moisture tension between 30 and 40 kPa through frequent irrigation (30‐40); and (iii) alternately allowing soil to dry to 80 kPa tension then irrigating to wet soil to 10 kPa (10‐80). Thus, there were six treatment combinations. The soil was a Molokai silty clay loam (Typic Torrox). Stalk population was 16% greater (P<0.05) in high than low N‐K treatments, whereas there was no significant effect of irrigation treatment on stalk population. In samples taken from 200 to 250 days after planting, leaf area index was about 30% greater in the 575‐551 than 225‐217 kg N‐K ha−1 treatments (P<O.OO1). Soil moisture was directly related to number of green leaves per stalk and inversely related to number of chlorotic leaves per stalk. Respective cane and crop growth (dry matter assimilation) rates were 25 and 24% higher in treatments receiving 575‐551 than 225‐217 kg N‐K ha−1 (P<O.O1). Cane and crop growth rates were 27 and 23% greater for the 10‐20 than 30‐40 and 10‐80 soil moisture treatments, with no significant difference between growth rates of the 30‐40 and 10‐80 soil moisture regimes. Based on sugar yields, N‐K fertilizer use efficiency was greatest for the 10‐20 soil moisture treatments and water use efficiency was greatest for the 575‐551 kg N‐K ha−1 treatments. Thus, we conclude that N‐K and soil moisture inputs should be balanced and at high levels to maximize production and the efficient use of inputs. Furthermore, these results support the management practices of frequent fertilization and irrigation which have been adopted by many growers of drip‐irrigated sugarcane.